Students’ Views about the Non-traditional Writing - Memiş, Esra Kabataş (Elsevier BV, 2014)
AbstractThe aim of this study was to determine university students’ views about the writing to learn activities. The study involved two the same level classes with total of 78 students (39 students in each classes) in a large university at eastern part of Turkey. Both of the groups wrote letter as writing activity. Students completed two writing activities and each student received feedback to it. The only difference between these groups was different audience for writing letter. While one groups’ audience is elementary students, the other groups’ audience is teacher. Students wrote letter about different two topics (matter and force). At the end of this writing to learn activities, students were administrated questionnaire to determine their beliefs about non-traditional activities of each group. Results showed that all of students determined writing is as a useful and instructive activity
Keywords: non-traditional writing; writing to learn; writing; 4. Education